2021
DOI: 10.1111/inr.12734
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorders and influencing factors during the COVID‐19 pandemic: A cross‐sectional study of frontline nurses

Abstract: To assess the extent of posttraumatic stress disorder (PTSD) symptoms and severity, factors motivating work continuation, and factors influencing PTSD development among frontline nurses caring for patients with COVID-19. Background: The COVID-19 pandemic has an emotional toll on nurses. Exposure to traumatic events associated with the pandemic places frontline nurses at risk for developing PTSD. Design: Cross-sectional study. Methods: Frontline nurses (n = 370) who cared for COVID-19 patients in three governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…PTSD has been shown to be a predictor for SI, suicide attempts, and death by suicide (Cooper et al, 2020; Panagioti et al, 2017; Stanley et al, 2019). Considering the early pandemic timeframe, nurses with secondary stress syndrome were found to have a higher incidence of anxiety, depression, SI, and the nursing workplace as a source of PTSD (Ariapooran et al, 2022; Bae et al, 2022; Bani Issa et al, 2022). It seems appropriate to broaden the mental health challenges code to include SI and PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD has been shown to be a predictor for SI, suicide attempts, and death by suicide (Cooper et al, 2020; Panagioti et al, 2017; Stanley et al, 2019). Considering the early pandemic timeframe, nurses with secondary stress syndrome were found to have a higher incidence of anxiety, depression, SI, and the nursing workplace as a source of PTSD (Ariapooran et al, 2022; Bae et al, 2022; Bani Issa et al, 2022). It seems appropriate to broaden the mental health challenges code to include SI and PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used tools that were not specific to work conditions. For instance, Bani Issa et al (2021) [ 42 ] found that 36.2% of participants in a sample of 370 nurses self-reported clinically relevant trauma symptoms, as assessed by the Post-Traumatic Diagnostic Scale. Similarly, Crowe et al (2021) [ 43 ] reported that 37.6% of nurses in their sample experienced severe traumatic stress symptoms, as assessed by the Impact of Event Scale–Revised.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the findings of recent studies have indicated that HCWs, especially females, face a higher risk of excessive stress and burnout, not only due to the likelihood of work overload, but also due the imbalance between professional and personal life commonly experienced by people in the healthcare sector. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the findings of recent studies have indicated that HCWs, especially females, face a higher risk of excessive stress and burnout, not only due to the likelihood of work overload, but also due the imbalance between professional and personal life commonly experienced by people in the healthcare sector. 11,12 Until May 2022, systematic searches for qualitative research focusing on work-related stress among HCWs were conducted using PubMed, Scopus, EMBASE, and Web of Science. To facilitate literature review, three compartments of PICO framework (population, intervention, comparison, and outcome) were considered in the search strategy process.…”
Section: Introductionmentioning
confidence: 99%